American Religious Traditions, Orthodoxy, and Commitment in Public Opinion toward Torture. Issue 1 (19th December 2014) - Kilburn, H. Whitt; Fogarty, Brian J.
Abstract: The conventional wisdom on evangelical American Protestant support for the use of torture on suspected terrorists is incorrect. With data from the 2008 American National Election Studies survey, we specify the interactive influence of religious traditions on attitudes toward torture by religious commitment and belief orthodoxy. Only at low orthodoxy, and low to average commitment, are Catholics, mainline, and black Protestants more likely to support torture than the unaffiliated; the effect for evangelical Protestants is null. Greater commitment moves most traditions and the unaffiliated toward increased opposition to torture. Stronger orthodoxy, however, leads to support for torture only for the unaffiliated. The findings persist given controls for demographic characteristics, party identification, left-right self-placement, and authoritarian values.